2006
DOI: 10.1038/sj.cdd.4402048
|View full text |Cite
|
Sign up to set email alerts
|

OPA1 alternate splicing uncouples an evolutionary conserved function in mitochondrial fusion from a vertebrate restricted function in apoptosis

Abstract: In most eucaryote cells, release of apoptotic proteins from mitochondria involves fission of the mitochondrial network and drastic remodelling of the cristae structures. The intramitochondrial dynamin OPA1, as a potential central actor of these processes, exists as eight isoforms resulting from the alternate splicing combinations of exons (Ex) 4, 4b and 5b, which functions remain undetermined. Here, we show that Ex4 that is conserved throughout evolution confers functions to OPA1 involved in the maintenance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
132
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(149 citation statements)
references
References 35 publications
13
132
0
1
Order By: Relevance
“…We recently showed that after dissipation of the mitochondrial membrane potential as well as in several in vivo model systems of mitochondrial dysfunction proteolytic processing of the fusion factor OPA1 is induced and that this is a key step in inducing fragmentation of dysfunctional mitochondria (Duvezin-Caubet et al, 2006). This is in line with other studies showing that dissipation of the mitochondrial membrane potential and inducing apoptosis also led to proteolytic processing of OPA1 (Ishihara et al, 2006;Olichon et al, 2007). OPA1 processing and mitochondrial fragmentation was observed in mouse embryonic fibroblasts derived from a knock-in mouse expressing an error-prone mitochondrial DNA Polymerase  (Trifunovic et al, 2004), the so-called "mutator mouse" (DuvezinCaubet et al, 2006).…”
Section: Mitophagy and Its Role In Mitochondrial Quality Controlsupporting
confidence: 78%
“…We recently showed that after dissipation of the mitochondrial membrane potential as well as in several in vivo model systems of mitochondrial dysfunction proteolytic processing of the fusion factor OPA1 is induced and that this is a key step in inducing fragmentation of dysfunctional mitochondria (Duvezin-Caubet et al, 2006). This is in line with other studies showing that dissipation of the mitochondrial membrane potential and inducing apoptosis also led to proteolytic processing of OPA1 (Ishihara et al, 2006;Olichon et al, 2007). OPA1 processing and mitochondrial fragmentation was observed in mouse embryonic fibroblasts derived from a knock-in mouse expressing an error-prone mitochondrial DNA Polymerase  (Trifunovic et al, 2004), the so-called "mutator mouse" (DuvezinCaubet et al, 2006).…”
Section: Mitophagy and Its Role In Mitochondrial Quality Controlsupporting
confidence: 78%
“…58,59 However, the S2 cleavage site of i-AAA is not present in Drosophila OPA1. 60 Ectopic overexpression of another mitochondrial protease, Rhomboid-7, could process dOPA1. 61 Our western blot analysis revealed similar patterns of dOPA1 isoforms in wild-type and mutant flies (Supplementary Figure S5d), further substantiating that dYME1L is unlikely to be required for OPA1 processing.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of mitochondrial dysfunction, including lowered ATP levels, loss of mtDNA and dissipation of the mitochondrial membrane potential across the IM, the short forms of OPA1 accumulate at the expense of the long OPA1 isoforms (Ishihara et al 2004;Duvezin-Caubet et al 2006;Baricault et al 2007;Olichon et al 2007;Guillery et al 2008). Stress-induced degradation of long OPA1 isoforms was found to be mediated by OMA1 (Ehses et al 2009;Head et al 2009).…”
Section: Mitochondrial Quality Controlmentioning
confidence: 93%